Thoracic and abdominal outgrowths in early pterygotes: a clue to the common ancestor of winged insects? - Prokop, Jakub; Rosová, Kateřina; Leipner, Angelika; Sroka, Pavel (Communications biology, 2023)
One of the fundamental questions in insect evolution is the origin of their wings and primary function of ancestral wing precursors. Recent phylogenomic and comparative morphological studies broadly support a terrestrial ancestor of pterygotes, but an aquatic or semiaquatic ancestor cannot be ruled out. Here new features of the branchial system of palaeodictyopteran larvae of several different instars of Katosaxoniapteron brauneri gen. et sp. nov. (Eugereonoidea) from the late Carboniferous collected at Piesberg (Germany) are described, which consist of delicate dorsolateral and lamellate caudal abdominal gills that support an aquatic or at least semiaquatic lifestyle for these insects. Moreover, the similar form and surface microstructures on the lateral abdominal outgrowths and thoracic wing pads indicate that paired serial outgrowths on segments of both tagmata presumably functioned as ancestral type of gills resembling a protopterygote model. This is consistent with the hypothesis that the wing sheaths of later stage damselfly larvae in hypoxic conditions have a respiratory role similar to abdominal tracheal gills. Hence, the primary function and driving force for the evolution of the precursors of wing pads and their abdominal homologues could be respiration.
Keywords: Phylogeny; Wings, Animal; Insecta; křídla zvířecí; Larva; larva; Animals; biologická evoluce; Biological Evolution; hmyz; zvířata; fylogeneze